Resilience and opportunity lessons from the U.S. Gulf Coast after Katrina and Rita - Liu, Amy. (Washington, D.C. Brookings Institution, 2011)
"Examines the roles of community grassroots and charitable organizations as well as national, state, and local governments in post-disaster recovery and reform in the education, health care, legal, and political systems and in land use planning. Focuses on rebuilding to achieve more resilient, prosperous, and equitable communities"--Provided by publisher.
Introduction / Richard Mizelle ... [et al.] -- Professing regional resilience / Kathryn A. Foster -- School by school : the transformation of New Orleans public education / Andre Perry and Michael Schwam-Baird -- Delivering high-quality, accessible health care : the rise of community centers / Karen DeSalvo -- Criminal justice reforms / Nadiene Van Dyke, Jon Wool, and Luceia LeDoux -- Systemic ethics reform in Katrina's aftermath / David A. Marcello -- Bringing New Orleans home : community, faith, and nonprofit-driven housing recovery / Kalima Rose -- Evacuation planning for vulnerable populations : lessons from the New Orleans city assisted evacuation plan / John L. Renne -- Come on in this house : advancing social equity in post-Katrina Mississippi / Reilly Morse -- A tale of uneven comebacks : community planning and neighborhood design on the Mississippi Gulf Coast / Mukesh Kumar -- No more "planning by surprise" : post-Katrina land use planning in New Orleans / Robert A. Collins -- Coastal restoration and protection and the future of New Orleans / Mark S. Davis -- Building data capacity to foster resilient communities / Allison Plyer and Elaine Ortiz -- Rise of community organizations, citizen engagement, and new institutions / Frederick Weil -- Plugging into the power of community : how social networks energize recovery / Ann Carpenter and Nancy Montoya -- Interracial alliance building in a resilient New Orleans / Jasmine Waddell, Silas Lee, and Breonne DeDecker -- Leadership for a more equitable Louisiana / James A. Joseph ... [et al.] -- The role of philanthropy in reducing vulnerability and promoting opportunity in the Gulf South / Ivye Allen, Linetta Gilbert, and Alandra Washington.
Keywords: Hurricane Katrina, 2005.; Hurricane Rita, 2005.; Social problems -- Gulf Coast (U.S.); Disaster relief -- Gulf Coast (U.S.); Emergency management -- Gulf Coast (U.S.); Emergency management -- United States -- Planning